Design Meets Neuroscience: A Preliminary Review of Design Research Using Neuroscience Tools. Issue 1 (March 2022) - Hu, Linna; Shepley, Mardelle McCuskey
The past decade has witnessed a burgeoning interest in the intersection of neuroscience and design. Recent advancements in tools for measuring brain activity enable design researchers to investigate how brain function supports mental processes, complementing self–report and behavioral measures in exploring design cognition. With the aim of providing a preliminary understanding of how design researchers have approached neuroscience to date, we examined (1) previously explored neural research topics, (2) available tools and their contributions and limitations, and (3) the challenges of conducting design research using neuroscience tools. We start with a brief overview of major neuroscience tools measuring brain activation including electroencephalography (EEG), magnetic resonance imaging (MRI), near–infrared spectroscopy (NIRS), and positron emission tomography (PET). We then present a review of design research specifically on neural processes involved in design thinking and creativity. Consistencies of brain activity across studies are identified. Distinct patterns of brain activation associated with specific comparisons (e.g., design thinking vs. problem–solving) observed in previous studies are also summarized. An introductory review of design research using neuroscience tools on design evaluation and aesthetics is then provided. In addition to the promises of the fast–growing interdisciplinary collaboration of design and neuroscience, we outline technical, practical, and experimental difficulties caused by the limits of neuroscience tools for design research studies.